Viscous Dissipation Impact on Hydromagnetic Flow on a Stretching Surface: A Numerical Study - Deepthi, V. V. L.; Raju, R. Srinivasa; Narla, V. K. (Communications in Mathematics and Applications, 2023)
. The influence of magnetic field and viscous dissipation on a non-Newtonian fluid flowing across a nonlinear stretching sheet is investigated in this investigation. Researchers use similarity transformations to make the governing nonlinear partial differential equations (PDE) into ordinary differential equations (ODE) and then solve them using the ND Solve code in Mathematica. In the process of enhance the values of Eckert number, the temperature profile gets enhanced, while the rise in magnetic parameter decreases the velocity boundary layer (BL) thickness. The applications of this investigation are found in several heating devices and industrial processes such as incandescent light bulbs, food production, and many more.
Keywords: Magnetic field; Eckert number; Nanofluid; Stretching surface; Viscous Dissipation.